Transforming Islamic education management: Strategies for efficiency and effectiveness - Kurniawan, Satunggale (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study examines the management strategies employed in Islamic education to enhance the efficiency and effectiveness of educational institutions, with a focused case study on Pondok Pesantren Manbaul Hikam Putat. Motivated by the increasing complexity of challenges faced by Islamic boarding schools amid educational modernization—such as constraints in human resources, funding, and infrastructure—this research adopts a qualitative case study approach to provide an in-depth analysis. The study investigates key managerial dimensions including organizational structure, human resource management, curriculum development, infrastructure, and financial governance. Findings indicate that the pesantren maintains a relatively well-structured and accountable organizational framework, coupled with a strong commitment to continuous professional development through regular training programs for educators. The curriculum effectively integrates religious teachings with general knowledge; however, it requires further refinement to align with contemporary workforce demands. Financially, the institution endeavors to achieve sustainability by developing internal business units, though it remains significantly dependent on community donations. Additionally, the study identifies the need for substantial improvements in educational facilities, particularly classrooms and laboratories. In summary, while the pesantren demonstrates generally effective education management practices, several strategic areas warrant further enhancement to meet evolving educational standards. This research contributes valuable insights for policymakers and practitioners aiming to strengthen the management of Islamic educational institutions facing similar modernization challenges.